Aminopropyl-Functionalized Silica CO2 Adsorbents via Sonochemical Methods - Gregory P. Knowles; Alan L. Chaffee (Journal of Chemistry)
Aminopropyl-functionalized hexagonal mesoporous silica (HMS) products, as are of interest for CO2 capture applications, were separately prepared by mixing aminopropyltrimethoxysilane (APTS) and HMS in toluene via a conventional stirred reactor and via sonication assisted methods, to investigate the potential of sonication to facilitate the preparation of products with higher tether loadings and correspondingly higher CO2 sorption capacities. Sonication was expected to improve both the dispersion of the substrate in the solvent and the diffusion of the silane throughout the mesoporous substrate. Structural properties of the products were determined by X-ray diffraction, N2 adsorption/desorption (77 K), helium pycnometry, and elemental analysis, and CO2 adsorption/desorption properties were determined via thermogravimetric and differential thermal analysis. The tether loadings of the sonication products (up to 1.8 tethers·nm−2) were found to increase with sonication time and in each case were greater than the corresponding product prepared by the conventional approach. It was also found that the concentration of the reagent mixture influenced the extent of functionalization, that the crude products cured effectively under N2 flow as under vacuum, and that rinsing the crude products prior to curing was not essential. Sonication products with higher tether loadings were found to exhibit higher CO2 sorption capacities as expected.